Cover Feature: High‐Throughput Platform for Novel Reaction Discovery (Chem. Eur. J. 50/2022). Issue 50 (3rd August 2022) - Lu, Xiao; Luo, Zhiji; Huang, Ruili; Lo, Donald C.; Huang, Wenwei
Abstract : Quaternary ammonium tag‐assisted purification (QATAP) : A quaternary ammonium compound containing a carboxylic acid demonstrates unique selectivity in weak cation‐exchange, solid‐phase extraction purification. This unique selectivity enables us to develop a high‐throughput reaction discovery platform. The advantages of this technology are the simple procedure and the required low‐cost equipment, making this platform accessible to most academic labs. More information can be found in the Research Article by W. Huang et al. (DOI: 10.1002/chem.202201421 ).